2023
DOI: 10.1051/0004-6361/202244584
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of carbon and sulfur isotope ratios in the Milky Way

Abstract: Context. Isotope abundance ratios provide a powerful tool for tracing stellar nucleosynthesis, evaluating the composition of stellar ejecta, and constraining the chemical evolution of the Milky Way. Aims. We aim to measure the 12C/13C, 32S/34S, 32S/33S, 32S/36S, 34S/33S, 34S/36S, and 33S/36S isotope ratios across the Milky Way. Methods. With the IRAM 30 meter telescope, we performed observations of the J = 2−1 transitions of CS, C33S, C34S, C36S, 13CS, 13C33S, and 13C34S as well as the J = 3−2 transitions of C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 72 publications
5
9
0
Order By: Relevance
“…We note that the derived X 13/18 across both galaxy centers are well constrained at a range of 6-8, which is similar to the Galactic Center value (Areal et al 2018). On the other hand, our derived X 12/13 values are higher than X 12/13 ∼ 25 found in our Galactic Center (Wilson & Rood 1994;Milam et al 2005;Yan et al 2023) as well as the central kiloparsec of NGC 3351 (Teng et al 2022). This is in line with the higher X 12/13 values varying from ∼40 to >100 that have been commonly found in other starburst galaxy centers or (U)LIRGs, likely due to higher inflow rates and/or stellar nucleosynthesis enrichment (Henkel et al 2014;Sliwa et al 2014Sliwa et al , 2017Tang et al 2019).…”
Section: Rangesupporting
confidence: 77%
“…We note that the derived X 13/18 across both galaxy centers are well constrained at a range of 6-8, which is similar to the Galactic Center value (Areal et al 2018). On the other hand, our derived X 12/13 values are higher than X 12/13 ∼ 25 found in our Galactic Center (Wilson & Rood 1994;Milam et al 2005;Yan et al 2023) as well as the central kiloparsec of NGC 3351 (Teng et al 2022). This is in line with the higher X 12/13 values varying from ∼40 to >100 that have been commonly found in other starburst galaxy centers or (U)LIRGs, likely due to higher inflow rates and/or stellar nucleosynthesis enrichment (Henkel et al 2014;Sliwa et al 2014Sliwa et al , 2017Tang et al 2019).…”
Section: Rangesupporting
confidence: 77%
“…The largest systematic uncertainty in deriving the hydrogen column density is in the [ 12 CO]/[ 13 CO] abundance ratio. This ratio varies by more than a factor of 5 within our Galaxy (e.g., Yan et al 2023), and our adopted ratio (N 12CO /N 13CO = 29 ± 15) is close to the carbon isotope ratio of [ 12 C]/[ 13 C] = 21 ± 5 near our Galactic center (Yan et al 2023). The lower abundance ratio there is attributed to more star formation in the past than in the outer Galactic radius.…”
Section: Rotation Diagrams and Hydrogen Column Densitysupporting
confidence: 78%
“…We found that linear functions fit both 12 CO and 13 CO reasonably well and derived T ex,12CO = 286 ± 30 K and T ex,13CO = 173 ± 17 K, and the total column densities N 12CO = (1.5 ± 0.3) × 10 19 cm −2 and N 13CO = (4.3 ± 0.5) ×10 18 cm −2 . However, the results seem unreasonable; the two excitation temperatures do not match, and the 12 CO column density is only ;3.5 times that of 13 CO, while the Galactic [ 12 C]/[ 13 C] abundance ratio is 20-100 (e.g., Yan et al 2023). We interpreted the results as an underestimation of the 12 CO columns of the lower-J levels due to the saturation of the absorptions; the deep absorption profiles change little as a function of the optical depth near the bottoms, where the S/N is very low due to the absorptions, and the fit cannot exclude solutions with moderate optical depths.…”
Section: Rotation Diagrams and Hydrogen Column Densitymentioning
confidence: 99%
“…This value is within the range of 30-70 dependent on the distance and the environment in the Galaxy (Wilson & Rood 1994) and similar to the conversion factor of 50, which has been used in previous observations in Purcell et al (2006), Sanhueza et al (2012), andVasyunina et al (2011). An average of 55.6 for 12 C/ 13 C in all sources is derived using the most recent (4.77 ± 0.81) R GC +(20.76 ± 4.61) in Yan et al (2023) with R GC from Table 1. The column density ratios for N[HNCO]/N[HCO + ] converting from [HNCO]/[HCO + ] are thus 0.57 and 3.06 for the line central emission at excitation temperatures of 37.5 and 150 K, respectively.…”
Section: Intensity Ratios and Column Density Ratios Of Hnco To Hco +supporting
confidence: 71%